Local and systemic immune responses induced by intranasal immunization with biomineralized foot-and-mouth disease virus-like particles - Li, Shuo; Zhao, Ruichong; Song, Hetao; Pan, Songjia; Zhang, Yun; Dong, Hu; Bai, Manyuan; Sun, Shiqi; Guo, Huichen; Yin, Shuanghui (Frontiers in Microbiology, 2023)
Introduction Foot-and-mouth disease virus (FMDV) infects the host by invading mucosal epithelial cells of the respiratory or digestive tract. Therefore, establishing a specific antiviral mucosal immune barrier can effectively block viral invasion. Methods We evaluated local mucosal and systemic immune responses elicited by intranasal immunization of mice with foot-and-mouth disease (FMD) calcium phosphate mineralized virus-like particles (CaP-VLPs) and tested whether three commercial mucosal adjuvants enhanced the immunogenicity of the antigen. The biosafety of the vaccine was verified through gross observation and pathological analysis of the lungs. Results CaP-VLPs effectively induced secretion of IgA (sIgA) from multiple sites in mouse mucosa and produced anti-FMD-specific IgG in the serum. Splenic lymphocytes specifically proliferated and secreted IFN-γ following antigen stimulation, indicating the vaccine can induce a certain level of cellular immune response. Finally, the pathological examination confirmed that CaP-VLPs did not cause substantial damage to the lungs of animals after immunization via mucosal administration. Notably, the vaccine mixed with S adjuvant increased the content of sIgA and serum IgG, and the high level of IgG in serum was maintained at least 7 weeks. Discussion Overall, this study reveals that FMD CaP-VLPs can induce good local mucosal immune and systemic immune response through intranasal immunization, and the immune response was specifically enhanced by S adjuvant. These data support that CaP-VLPs-S as a candidate mucosal vaccine for the prevention of FMD vaccine infection.